Enhancing ethanol yields in corn dry grind process by reducing glycerol production. Issue 5 (26th August 2020) - Kumar, Deepak; Jansen, Mickel; Basu, Rahul; Singh, Vijay
Abstract: Background and objectives: Reducing glycerol production, a major by‐product produced during fermentation by yeast Saccharomyces cerevisiae, can improve the ethanol productivity in corn dry grind process. This study investigates the potential of glycerol reduction using an advanced engineered yeast strain and determines the effect of enzyme dosage, pH, and temperature on the granular starch hydrolysis (GSH) process efficiency using both conventional yeast and advanced yeast. Findings: Ethanol yields in GSH process were found maximum at enzyme dosage 4.8 kg/MT grains and remained unchanged with further increase in dosage. The glycerol production was reduced by more than 50% with use of advanced enzymes compared to the conventional yeast and resulted in 2.2–3.8% higher final ethanol concentrations. Performances of both yeast were reduced and lead to stuck fermentation at 36°C temperature. Conclusions: Use of advanced yeast strains can improve the ethanol yields by reducing glycerol production in GSH process; however, the ethanol yields are highly dependent on the process conditions, especially enzyme loadings and temperature. Significance and novelty: GSH process is expected to produce lower glycerol compared to conventional dry grind process. This research demonstrated that advanced engineered yeasts can reduce the glycerol production in GSH process also, improving the process yields and profitability.